1996
DOI: 10.1046/j.1420-9101.1996.9020173.x
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid zone between two subspecies of Chorthippus parallelus. X‐chromosome variation through a contact zone

Abstract: Summary Two grasshopper subspecies, Chorthippus parallelus parallelus (Cpp) and Chorthippus parallelus erythropus (Cpe), meet along the Pyrenees where they hybridize and produce a hybrid zone. A contact zone located in the Col de Portalet has been analyzed for the distribution of chromosome markers on the sex (X) chromosome in pure and hybrid populations. C‐banding allowed us to distinguish both pure subspecific forms and recombinant forms, and to demonstrate their different frequencies through the contact zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 14 publications
5
30
1
1
Order By: Relevance
“…The clinal distribution of Wolbachia strain infections along a northsouth gradient in the populations here studied and the overall decrease of the infection levels across this transect (Figure 1) are striking. Nevertheless, these alone are not evidence that Wolbachia acts as a reproductive barrier in this system, although it is very intriguing that the peak incidence of co-infection in Sallent de Gállego coincides with those of some cytogenetic markers described in previous studies (Gosálvez et al, 1988;Serrano et al, 1996), which reported a shift from 100 to 0% in the frequency of a distal heterochromatic band in the X chromosome (Pband) characteristic of Cpp between Corral de Mulas and Sallent de Gállego. Another study proposed that there was an incompatibility between this P-band region and cytoplasmic factors presumed to be present in Cpe cells (Virdee and Hewitt, 1992).…”
Section: No Infection B Infection F Infection Coinfectionmentioning
confidence: 68%
“…The clinal distribution of Wolbachia strain infections along a northsouth gradient in the populations here studied and the overall decrease of the infection levels across this transect (Figure 1) are striking. Nevertheless, these alone are not evidence that Wolbachia acts as a reproductive barrier in this system, although it is very intriguing that the peak incidence of co-infection in Sallent de Gállego coincides with those of some cytogenetic markers described in previous studies (Gosálvez et al, 1988;Serrano et al, 1996), which reported a shift from 100 to 0% in the frequency of a distal heterochromatic band in the X chromosome (Pband) characteristic of Cpp between Corral de Mulas and Sallent de Gállego. Another study proposed that there was an incompatibility between this P-band region and cytoplasmic factors presumed to be present in Cpe cells (Virdee and Hewitt, 1992).…”
Section: No Infection B Infection F Infection Coinfectionmentioning
confidence: 68%
“…These phylogroups are likely to have originally migrated north from an Iberian refugium, but this must have occurred much earlier than most phylogeographic reconstructions of variation in this area suggest. The Pyrenees are a major 'suture zone' with many species or subspecies meeting in this region, but most, such as the well-characterised Chorthippus parallelus hybrid zone, seem to occur in relatively narrow secondary hybrid zones along the main mountain ridge (eg Butlin et al, 1992;Serrano et al, 1996). They have usually been interpreted as a single broad contact, occurring independently in different valleys, but all taking place following the last climatic amelioration.…”
Section: Lj Spooner and Mg Ritchiementioning
confidence: 99%
“…There is a further interstitial band (H-band) that is characteristic of some natural hybrid individuals and populations. The recombinants for these bands have been found in the hybrid zone, rendering a total of 8 different X types [Gosálvez et al, 1988;Serrano et al, 1996;Bella et al, 2007]. In total, 103 individuals from the hybrid population of Portalet were analysed.…”
Section: Chromosome Markersmentioning
confidence: 99%
“…In total, 103 individuals from the hybrid population of Portalet were analysed. This population was selected because it has individuals harboring the distinct X morphs [Serrano et al, 1996] and has recently been characterized for the presence of Wolbachia [Zabal-Aguirre et al, 2010]. Wolbachia infection was analysed by PCR, resulting in 73 samples that were infected and 30 that were uninfected.…”
Section: Chromosome Markersmentioning
confidence: 99%
See 1 more Smart Citation